Hubungan Pengetahuan Ibu Dengan Pemberian Imunisasi Dasar Pada Bayi di Klinik Bidan Sri Wulandari Tahun 2023 - Dewi Safitri; Dewi Sartika Hutabarat; Sastiani Br.Ginting; Ayu Rosarita; Syahrin Sakinah (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2023)
Early Initiation of Breastfeeding is the process of a baby breastfeeding immediately after birth, where the baby is allowed to look for the mother's own nipple (not having the nipple offered). Early initiation of breastfeeding will greatly help in the continuation of exclusive breastfeeding (breast milk only) and the duration of breastfeeding. IMD has been shown to extend the duration of breastfeeding, increase the chances of a baby being breastfed in the first months of life, and can also contribute to increased exclusive breastfeeding. Babies who practice IMD also appear to interact more with their mothers and cry less (UNICEF, 2018; WHO, 2019 ). This type of research is analytical, namely the researcher will analyze the relationship between maternal knowledge and basic immunization provision, with a cross-sectional design, namely data on the mother's level of knowledge and basic immunization provision. The research was conducted at the Midwife Sri Wulandari clinic, S.Tr.Keb in 2023. The research was conducted April to June 2022. The population is relatively small, namely under 100 people. From the description above, the author used a total sampling technique, namely 52 mothers with 1 year old babies.